Tracheal myoepithelioma resected by using flexible video bronchoscope: a case report and review of the literature - Meng, Xiaosheng; Meng, Jiguang; Cao, Yaping (Frontiers in Oncology, 2026)
BackgroundTracheal myoepithelioma is a rare, low-grade malignant tumor originating from salivary gland tissue. This article presents a case of tracheal myoepithelioma without clinical symptoms, diagnosed and treated using flexible video bronchoscopy.Case ReportA 44-year-old male patient, asymptomatic for respiratory issues, was found to have a tracheal mass during a routine chest CT scan. The mass showed no significant changes over the course of one year. Upon admission, flexible video bronchoscopy revealed a coral-like neoplasm. The tumor was resected using a high-frequency electrocautery loop, followed by cryotherapy to remove residual tissue. Postoperative pathological examination confirmed the diagnosis of myoepithelioma. Three months later, follow-up flexible video bronchoscopy demonstrated good mucosal healing at the original tumor site, and chest CT showed no evidence of infiltration. The patient reported no discomfort during this period.ConclusionAlthough tracheal myoepitheliomas are rare, they should be considered in the differential diagnosis of tracheal masses. Minimally invasive interventional therapy via flexible video bronchoscopy may serve as a valuable diagnostic and therapeutic approach.